2019
DOI: 10.18203/issn.2454-2156.intjscirep20194648
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of repair failure and associated factors among women undergone obstetric fistula repair in Bahir Dar Hamlin Fistula Center, Amhara Region, Northwest Ethiopia

Abstract: <p class="abstract"><strong>Background:</strong> Globally, prevention and repair of obstetric fistula remains a challenge, Ethiopia is one of the high-burden countries that constitute to the high fistula belt in the world.</p><p class="abstract"><strong>Methods:</strong> Cross sectional study was conducted from 1st April 2018 to 1st May 2018 on women who had undergone obstetric fistula repair from 1st January 2013 to 30th December 2017. Systematic sampling technique wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 24 publications
5
25
1
Order By: Relevance
“…In this study, factors affecting obstetric fistula repair failure demonstrated that women who had a labor duration of more than 48 h were two times more likely to have an obstetric fistula repair failure than women who had a labor duration of less than 48 h. This finding was comparable with previous studies done in Bahir Dar (Ethiopia) [ 18 ] and Rwanda [ 19 ]. The possible explanation might be due to the presence of any type of delay, whether indecision or delay in reaching a health facility or delay in getting the quality of care, which can increase the duration of labor and lead to longer obstructed labor.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In this study, factors affecting obstetric fistula repair failure demonstrated that women who had a labor duration of more than 48 h were two times more likely to have an obstetric fistula repair failure than women who had a labor duration of less than 48 h. This finding was comparable with previous studies done in Bahir Dar (Ethiopia) [ 18 ] and Rwanda [ 19 ]. The possible explanation might be due to the presence of any type of delay, whether indecision or delay in reaching a health facility or delay in getting the quality of care, which can increase the duration of labor and lead to longer obstructed labor.…”
Section: Discussionsupporting
confidence: 89%
“…According to the findings of this study, women with Goh Type 4 fistulas were 3.9 times more likely than women with Goh Type 1 fistulas to have obstetric fistula repair failure. This finding is supported by the findings of a study conducted in the Bahir Dar Hamlin fistula center (Ethiopia) [ 18 ]. The possible explanation might be due to the close of the fistula to the external urethral meatus or the hymen, largely affecting the function of the urinary system, which leads to high risk of fistula repair failure [ 35 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations